Training of researchers on Integrity in Research: spaces and subsidies related to ethical care in educational research (Práxis Educativa, 2023)
In this article, ethics and integrity in research in the researcher-professor training process are discussed. Ethical weaknesses present in the various stages of the research are identified and the training of the researcher in Education for ethical conduct and research integrity in undergraduate and graduate courses are questioned. It was a qualitative, exploratory and review study developed from articles available at the journal database of the Coordination for the Improvement of Higher Education Personnel (CAPES) and the Scientific Electronic Library Online (SciELO), published between 2012 and 2022. The results indicate that in undergraduate and graduate courses in Education, ethical fragilities in research can be approached in several spaces. The undergraduate curriculum components and research initiation and extension activities are discussion spaces for ethical conduct and integrity in research.  In graduate studies in Education, curricular components, research groups and guidance activities are spaces for promoting integrity and ethics in research.Keywords: Ethics in research. Integrity in research. Professor-researcher training.